THE CONSEQUENCES OF TERMINATION OF EMPLOYMENT RELATIONSHIP DUE TO DISCRIMINATION - Tasić, Anđelija; Obradović, Goran (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
This article focuses on the procedural norms concerning antidiscrimination and labour rights protection. By analyzing concrete legal norms, the authors attempt to address the key question: what is the appropriate way of ensuring legal protection for victims of unlawful termination due to discrimination? The fact is that two different legal procedures contain different rules about time limit for initiating civil proceedings, filing a claim or motions, as well as didderent rules on the burden of proof. These complex issues have been insufficiently addressed in theory and practice. For the purpose of overcoming this problem, the authors provide an insight into the comparative law solutions which may be used as guidelines in prospective legislative efforts and adjusted to the specific features of the legal system in the Republic of Serbia.
Keywords: discrimination; termination of employment relationship; returning an employee to work; personal characteristics